Hubungan Asupan Natrium dengan Tekanan Darah pada Lansia Di Posyandu Lansia "Ngudi Waras" Desa Blulukan Kecamatan Colomadu, Karanganyar, Jawa Tengah - Najwa, Siti Adidatun, Siti Zulaekah, A., M.Si, Nur Lathifah Mardiyati, S.Gz., M.S (2016)
Background : Natural aging process decreases the function of various organs. For instance, it declines the function of blood vessels in elderly group. Degeneratif disease that is common in the elderly group with high morbidity and mortality rate is high blood pressure. There are several factors that can affect blood pressure in which sodium intake is one of them. Based on data published by Riskesdas 2013, national prevalence of high blood pressure was 25,8%. Objective : To find out the correlation between sodium intake with blood pressure in the elderly in Posyandu "Ngudi Waras" Blulukan Village Colomadu Subdistrict, Karanganyar, Central Java. Research Method : Type of research was an observational study with cross sectional design. There were 36 respondents chosen by consecutive sampling technique. Sodium intake was obtained by interview using a semi quantitative FFQ, while blood pressure was obtained from the cadres who had measured their blood pressure records. Shapiro-Wilk is used in normality data test while Pearson Product Moment is used in correlation test. Results : There is a correlation of sodium intake (p=0,000) and blood pressure (p=0,000) in the elderly in Posyandu "Ngudi Waras" Blulukan Village Colomadu Subdistrict, Karanganyar, Central Java. Conclusion : There is a correlation between sodium intake with blood pressure in the elderly in Posyandu "Ngudi Waras" Blulukan Village Colomadu Subdistrict, Karanganyar, Central Java. Keyword : Sodium intake, blood pressure.